Intramolecular carbolithiation cascades as a route to a highly strained carbocyclic framework: competition between 5-exo-trig ring closure and proton transfer - Bailey, William F.; Fair, Justin D. (Beilstein Journal of Organic Chemistry, 2013)
The preparation of fairly strained carbocyclic ring systems by intramolecular 5-exo-trig ring closure has been well documented, and the absence of proton transfers that would compromise such cyclizations is a hallmark of this chemistry. In an effort to explore the limitations of this approach to more highly strained systems, the preparation of a stellane (tricyclo[3.3.0.03,7]octane) framework by an intramolecular carbolithiation cascade involving three coupled 5-exo-trig cyclizations of the vinyllithium derived from 2-bromo-4-vinyl-1,6-heptadiene by lithium–bromine exchange was investigated. The cascade does not afford the stellane; rather, the cascade is terminated after two cyclizations by a proton transfer that occurs by an intermolecular process catalyzed by trace amounts of endo-5-methyl-2-methylenebicyclo[2.2.1]heptane present in reaction mixtures as a consequence of inadvertent quenching of an intermediate alkyllithium during prolonged reaction times at room temperature.
Keywords: carbolithiation cascade; carbometallation; intramolecular carbolithiation; intermolecular proton transfer; lithium–halogen exchange; strained hydrocarbons

(untitled) - Drozd, V. N.; Ustynyuk, Yu. A.; Tsel’eva, M. A.; Dmitriev, L. B. (J. Gen. Chem. USSR, 1968)
Zh. Obsch. Khim. 1968, 38, 2144.

(untitled) - Drozd, V. N.; Ustynyuk, Yu. A.; Tsel’eva, M. A.; Dmitriev, L. B. (J. Gen. Chem. USSR, 1969)
Zh. Obsch. Khim. 1969, 39, 1991.

(untitled) - St. Denis, J.; Dolzine, T.; Oliver, J. P. (J. Am. Chem. Soc., 1972)

(untitled) - Bailey, W. F.; Khanolkar, A. D.; Gavaskar, K.; Ovaska, T. V.; Rossi, K.; Thiel, Y.; Wiberg, K. B. (J. Am. Chem. Soc., 1991)

Advances in Detailed Reaction Mechanisms - Bailey, W. F.; Ovaska, T. V. (Mechanisms of Importance in Synthesis, 1994)

Organolithiums: Selectivity for Synthesis - Clayden, J. (Pergamon Press, 2002)

The Chemistry of Organolithium Compounds - Fañanás, F. J.; Sanz, R. (Intramolecular carbolithiation reactions, 2004)

(untitled) - Bailey, W. F.; Salgaonkar, P. D.; Brubaker, J. D.; Sharma, V. (Org. Lett., 2008)
And references therein.

(untitled) - Mealy, M. J.; Bailey, W. F. (J. Organomet. Chem., 2002)
See for a review.

(untitled) - Bailey, W. F.; Khanolkar, A. D. (Tetrahedron Lett., 1990)

(untitled) - Bailey, W. F.; Nurmi, T. T.; Patricia, J. J.; Wang, W. (J. Am. Chem. Soc., 1987)

(untitled) - Bailey, W. F.; Rossi, K. (J. Am. Chem. Soc., 1989)

(untitled) - Bailey, W. F.; Khanolkar, A. D. (J. Org. Chem., 1990)

(untitled) - Bailey, W. F.; Khanolkar, A. D.; Gavaskar, K. V. (J. Am. Chem. Soc., 1992)

(untitled) - Bailey, W. F.; Khanolkar, A. D. (Organometallics, 1993)

(untitled) - Bailey, W. F.; Patricia, J. J.; DelGobbo, V. C.; Jarret, R. M.; Okarma, P. J. (J. Org. Chem., 1985)

(untitled) - Bailey, W. F.; Punzalan, E. P. (J. Am. Chem. Soc., 1994)

(untitled) - Webster, O. W.; Sommer, L. H. (J. Org. Chem., 1964)

(untitled) - Sauers, R. R.; Kelly, K. W. (J. Org. Chem., 1970)

Ger. Patent - Cohen, C. A. (Cyclopentane-1,3-Dicarboxylic Acids, 1957)

(untitled) - Khoury, P. R.; Goddard, J. D.; Tam, W. (Tetrahedron, 2004)

(untitled) - Bailey, W. F.; Punzalan, E. R. (J. Org. Chem., 1990)